2019
DOI: 10.2337/cd17-0066
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Underwater Treadmill Training on Glycemic Control, Blood Lipids, and Health-Related Fitness in Adults With Type 2 Diabetes

Abstract: IN BRIEF A large number of adults with type 2 diabetes experience comorbidities that discourage physical activity and hinder regular participation in land-based exercise programs. An aquatic exercise program is an innovative exercise modality that incorporates combined aerobic and resistance exercise. The purpose of this study was to determine if an underwater treadmill walking program featuring gradual and progressive increases in walking speed and duration has a positive effect on glycemic control, metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
0
13
0
3
Order By: Relevance
“…Footwear considered appropriate must have a thick sole, su cient width and depth to accommodate a sock and the foot comfortably, the inside of the footwear must be soft and seamless, adjustable with laces or velcro, offering total protection to the toes (round or square toe), sole up to three centimeters, and made with soft raw material [7,19,34]. It should be noted that the use of inappropriate shoes has been described in the literature as a relevant factor for the development of the risk of ulceration and peak plantar pressure [18,[35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Footwear considered appropriate must have a thick sole, su cient width and depth to accommodate a sock and the foot comfortably, the inside of the footwear must be soft and seamless, adjustable with laces or velcro, offering total protection to the toes (round or square toe), sole up to three centimeters, and made with soft raw material [7,19,34]. It should be noted that the use of inappropriate shoes has been described in the literature as a relevant factor for the development of the risk of ulceration and peak plantar pressure [18,[35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 29 included studies, eight articles [30,32,34,35,37,[39][40][41] with 441 patients, demonstrated that structured physical exercise interventions were associated with an increase of 51.59 meters in walking performance evaluated by the 6-minute-walk test (6MWT) (95% CI 7.55% to 95.63%; I 2 92%; p for heterogeneity < 0.01) as compared with control (Figure 2, panel 1 (A)).…”
Section: Walking Performancementioning
confidence: 99%
“…Pada metode aktivitas fisik , ditemukan dalam lima studi bahwa latihan kombinasi, dibandingkan dengan latihan aerobic, resistensi, maupyn latihan peregangan, mmeiliki manfaat yang lebih baik bagi penderita DMT2. Intensitas latihan mempengaruhi profil lipid karena latihan aerobic maupun resistensi intensitas sedang dan jangka waktu yang pendek tidak mengurangi LDL maupun TG (25), hal itu berbeda dengan hasil penelitian dari rahbar (2017) bahwa pelatihan aerobic dengan intensitas sedang dalam waktu 8 minggu mempiliki dampak positif terhadap pengendalian parameter biokimia, yaitu penurunan kadar glukosa darah puasa, tingkat kolesterol, TG maupun LDL (26). Pelatihan latihan aerobik meningkatkan efektivitas perawatan medis pada DMT2.…”
Section: Gambar 1 Diagram Flow Dan Pemilihan Artikelunclassified
“…Praktek program aktivitas fisik berkorelasi dengan kontrol glikemik yang lebih baik dan profil lipid karena menurunkan kadar glukosa darah puasa (26,27,29,40,41), dan tingkat postprandial (28,41), hemoglobin terglikasi (HbA1c) (26), resistensi insulin (27,29,40), dan kadar insulin puasa (27,29,40). Selain itu juga diamati penurunan pada kadar Trigliserida (TG) (25,26,40,41) , kolesterol total (26,40,41), High Density Lipoprotein (HDL) (25,41), dan Low Density Lipoprotein (LDL) (25,26,40,41).…”
Section: Gambar 1 Diagram Flow Dan Pemilihan Artikelunclassified
See 1 more Smart Citation